2005
DOI: 10.1111/j.1742-4658.2004.04542.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant defences in cybrids harboring mtDNA mutations associated with Leber's hereditary optic neuropathy

Abstract: Oxidative stress and imbalance between free radical generation and detoxification may play a pivotal role in the pathogenesis of Leber's hereditary optic neuropathy (LHON). Mitochondria, carrying the homoplasmic 11778/ND4, 3460/ND1 and 14484/ND6 mtDNA point mutations associated with LHON, were used to generate osteosarcoma‐derived cybrids. Enhanced mitochondrial production of reactive oxygen species has recently been demonstrated in these cybrids [Beretta S, Mattavelli L, Sala G, Tremolizzo L, Schapira AHV, Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 48 publications
4
84
0
Order By: Relevance
“…Studies analyzing the impact of mutations in mtDNA-encoded genes on ROS production in different mitochondrial disease models (fibroblasts, transmitochondrial cybrids and neuronal NT2 cells) have frequently revealed increased ROS levels (Pitkanen and Robinson, 1996;Rana et al, 2000;Geromel et al, 2001;Wong et al, 2002;Beretta et al, 2004;Floreani et al, 2005;Gonzalo et al, 2005;Vives-Bauza et al, 2006). The deleterious effect of each mutation could be influenced by the genetic background of a specific patient, as the biosynthesis of the OXPHOS complexes implies the interaction between many different subunits and regulatory factors.…”
Section: Role Of the Mtdna Genetic Background On The Rc Dysfunction Amentioning
confidence: 99%
See 1 more Smart Citation
“…Studies analyzing the impact of mutations in mtDNA-encoded genes on ROS production in different mitochondrial disease models (fibroblasts, transmitochondrial cybrids and neuronal NT2 cells) have frequently revealed increased ROS levels (Pitkanen and Robinson, 1996;Rana et al, 2000;Geromel et al, 2001;Wong et al, 2002;Beretta et al, 2004;Floreani et al, 2005;Gonzalo et al, 2005;Vives-Bauza et al, 2006). The deleterious effect of each mutation could be influenced by the genetic background of a specific patient, as the biosynthesis of the OXPHOS complexes implies the interaction between many different subunits and regulatory factors.…”
Section: Role Of the Mtdna Genetic Background On The Rc Dysfunction Amentioning
confidence: 99%
“…proposed as the main contributors to the pathogenesis of LHON (Wong et al, 2002;Floreani et al, 2005;Beretta et al, 2006;Sala et al, 2008). Our group analyzed the effect of the most common LHON mutations that lead to complex I deficiency on the assembly of the native mitochondrial RC complexes, and also checked whether distinct mitochondrial genetic backgrounds differentially affected this process (Pello et al, 2008).…”
Section: Role Of the Mtdna Genetic Background On The Rc Dysfunction Amentioning
confidence: 99%
“…Subsequent analysis of these cybrids (11) have revealed partial complex I and site I respiration defects, reduced ATP production, increased mitochondrial ROS production, sensitization of the mitochondrial permeability transition pore (mtPTP) with predilection to apoptosis, and oxidative stress-induced inhibition of the excitatory glutamate transporter 1 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…An enhanced ROS generation has been observed in inherited complex I deficiencies (Pitkanen and Robinson, 1996;Luo et al, 1997). It has been reported that transmitochondrial cytoplasmatic hybrids or cybrids (Vergani et al, 1995) carrying the three most common Leber's hereditary optic neuropathy pathogenic mutations in complex I subunit genes show a partial respiratory defect as well as a significant increase in ROS production (Floreani et al, 2005).…”
Section: Discussionmentioning
confidence: 99%